Single-Agent Thalidomide for Treatment of Malignant Paraganglioma of the Organ of Zuckerkandl - Mackenzie L. Shindorf; Prabir K. Chaudhuri (Case Reports in Medicine)
The standard of care for benign pheochromocytomas and paragangliomas is surgical resection; however, there is no definitive curative or standard therapy for the treatment of malignant pheochromocytomas or paragangliomas. Current therapeutic options include surgical resection, chemotherapy (CVD therapy), MIBG-radiotherapy, somatostatin analogues, and combination targeted therapies such as temozolomide and thalidomide. Although some patients demonstrate short-lived responses to these various therapies, there has been no statistically significant survival benefit with any of the current regimens and therefore the aim is palliation and symptom control. Here, we present a 38-year-old man found to have an unresectable metastatic paraganglioma located in the Organ of Zuckerkandl who has been treated with single-agent thalidomide for over 15 years with minimal growth and stabilization of metastatic lesions. The management of our patient with single-agent therapy for this extended period of time challenges the efficacy and role of chemotherapy and other accepted therapies for malignant pheochromocytoma and paraganglioma.